1984
DOI: 10.1093/nar/12.21.8001
|View full text |Cite
|
Sign up to set email alerts
|

Tandemly arranged variant 5S ribosomal RNA genes In the yeastSaccharomyces cerevisiae

Abstract: Most of the ribosomal R-NA genes of the yeast Saccharomyces cerevisiae are about 9 kilobases (kb) in size and encode both the 35S rRNA (processed to produce the 25S, 18S, and 5.8S species) and 5S rRNA. These genes are arranged in a single tandem

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…The bent character of the 5S rDNA that rotationally phases NCPs (ref. 22 and this work) has been described (23). In conclusion, sequenceintrinsic and supercoil-induced curvatures attract and helically orient NCPs.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…The bent character of the 5S rDNA that rotationally phases NCPs (ref. 22 and this work) has been described (23). In conclusion, sequenceintrinsic and supercoil-induced curvatures attract and helically orient NCPs.…”
supporting
confidence: 52%
“…Four evenly distributed cleavage sites map on the 5S fragment ( Fig. 1D) (22). Uniformly labeled DNA c was reconstituted and the monomeric complex was digested with MN.…”
mentioning
confidence: 99%
“…Sequence analysis determined a match with the EcoRI B fragment of the rDNA repeat that includes the 5 S rRNA gene and the nontranscribed spacer region ( JEMTLAND et al 1986). Our restriction map of pFS22 is identical to published maps of the yeast ribosomal RNA gene (MCMAHON et al 1984;JEMTLAND et al 1986) (Figure 2). Analysis of rDNA: :LEU2 and rDNA::URA3 integrative recombinant mutants Complementation of m j 9 -l by the 5 S rRNA gene suggested that mop-1 might be a mutation of the rDNA.…”
Section: Methodssupporting
confidence: 84%
“…shown), indicating the PSE-like sequence and at least one _-U6 RNA repeat are dispensable. The last 6 bp of the third direct repeat are also found immediately upstream of the initiation site of both the repeated and variant yeast 5S rRNA genes (45,53), but substitution of this hexamer (In-sub, Fig. 6A) also had no effect on transcription in vitro or in vivo (data PS wnot shown).…”
Section: Resultsmentioning
confidence: 97%